Novel Chalcone-Based Fluorescent Human Histamine H3 Receptor Ligands as Pharmacological Tools - Stark, Holger (Frontiers in Systems Neuroscience, 2012)
Novel fluorescent chalcone-based ligands at human histamine H3 receptors (hH3R) have been designed, synthesized and characterized. Compounds described are non-imidazole analogues of ciproxifan with a tetralone motif. Tetralones as chemical precursors and related fluorescent chalcones exhibit affinities at hH3R in the same concentration range like that of the reference antagonist ciproxifan (hH3R pKi value of 7.2). Fluorescence characterization of our novel ligands shows emission maxima about 570 nm for yellow fluorescent chalcones and ≥600 nm for the red fluorescent derivatives. Interferences to cellular autofluorescence could be excluded. All synthesized chalcone compounds could be taken to visualize hH3R proteins in stably transfected HEK-293 cells using confocal laser scanning fluorescence microscopy. These novel fluorescent ligands possess high potential to be used as pharmacological tools for hH3R visualization in different tissues.